(untitled) (REVISTA NODO, 2024)
Photographic dossier authored by Norma Patiño. It is a series of portraits of women artists and activists representing a situation in a context of criticism against gender violence, through a performative action. Each of these women portrayed has a commitment to other women through their own language and personal work.